2017
DOI: 10.1007/s00170-017-0443-6
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic 3D labs- and organs-on-chips obtained by lithography-based ceramic manufacture

Abstract: In this study, we present a novel approach for the design and development of three-dimensional monolithic ceramic microsystems with complex geometries and with potential applications in the biomedical field, mainly linked to labson-chips and organs-on-chips. The microsystem object of study stands out for its having a complex three-dimensional geometry, for being obtained as a single integrated element, hence reducing components, preventing leakage and avoiding post-processes, and for having a cantilever porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…As an example of the aforementioned unhealthy behavior of hMSCs, recent studies have demonstrated how the number of cells adhered is reduced if mitochondria have diminished electron transport and how this is directly linked to the progressive spheroidal configurations, apoptotic behavior, and final detachment [29]. Taking into consideration the biofunctionalization post-process performed by using the hMSCs-CM, we would like to mention that the coating improves hMSCs adhesion up to a 30–40%, when compared to the use of uncoated microsystems, as previous studies by our team have shown [12,23,24,26]. However, the manufactured layers can be also used for culturing other cell types and even hMSCs, just after micro-injection and polishing, without the need for a final biofunctionalization step.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As an example of the aforementioned unhealthy behavior of hMSCs, recent studies have demonstrated how the number of cells adhered is reduced if mitochondria have diminished electron transport and how this is directly linked to the progressive spheroidal configurations, apoptotic behavior, and final detachment [29]. Taking into consideration the biofunctionalization post-process performed by using the hMSCs-CM, we would like to mention that the coating improves hMSCs adhesion up to a 30–40%, when compared to the use of uncoated microsystems, as previous studies by our team have shown [12,23,24,26]. However, the manufactured layers can be also used for culturing other cell types and even hMSCs, just after micro-injection and polishing, without the need for a final biofunctionalization step.…”
Section: Resultsmentioning
confidence: 98%
“…Alternative approaches relying on the combination of multi-scale processes, such as mask-based lithography and high-precision direct laser writing (by two-photon polymerization), also allow for the generation of multi-scale organs-on-chips [25], although their productivity (parts manufactured per time unit) is still far from matching the performance of mass-produced systems by micro-injection molding, as presented here. Nevertheless, in terms of geometrical complexity and integration level [26], additive procedures remain unrivalled, so further synergies between processes may prove highly beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional bioceramic-based microsystems are currently manufactured by additive manufacturing such as lithography-based ceramic manufacturing , and laser sintering . These fabrication methods accelerate fabrication processes and reduce cost and production time .…”
Section: Alternative Cell Contacting Materials In Pdms-based Devicesmentioning
confidence: 99%
“…However, Bauer et al has designed and produced an affordable FDM printed testing apparatus to detect malaria with a cost efficient [55]. Again, thanks to the pore structure obtained by the lithography-based ceramic manufacturing (LCM) method, LOC acts as a membrane with separating cell culture chambers at different levels, which imitates the typical configuration of transwell assays [56]. Furthermore, in a SLA-based printer, an LOC capable of detecting H2O2 and glucose can be produced under $1 [57].…”
Section: Additive Manufacturing Of Lab On a Chipsmentioning
confidence: 99%